Usability Measurement and Evaluation of E-Learning to Support the Training Program for Academic Staff (Pengukuran Usability dan Evaluasi E-Learning untuk Program Pelatihan bagi Tenaga Kependidikan) - theresia wati; Henki Bayu Seta; Ika Nurlaili Isnainiyah (BBPSDMP KOMINFO MAKASSAR, 2017)
This article discusses the usability measurement and evaluation of e-learning being used as a media for the academic staff training program of UPN